2023
DOI: 10.3390/jcm12062312
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Lidocaine Infusion in High-Risk Vascular Surgery—A Randomized, Double-Blind, Placebo-Controlled Single-Center Clinical Trial

Abstract: Background: In perioperative pain control, adjuvants such as lidocaine can reduce opioid consumption in a specific type of surgery. The aim of this single-center prospective double-blinded randomized controlled trial was to determine opioid consumption in the perioperative period in patients receiving continuous lidocaine infusion. Methods: Patients undergoing elective abdominal aorta and/or iliac arteries open surgery were randomized into two groups to receive 1% lidocaine or placebo at the same infusion rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…The data collected from the study by Gajniak et al involved patients undergoing subrenal major aortic surgery [ 11 ]. In the original study no differences were observed between the groups considering comorbidities, surgical techniques and depth of anesthesia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data collected from the study by Gajniak et al involved patients undergoing subrenal major aortic surgery [ 11 ]. In the original study no differences were observed between the groups considering comorbidities, surgical techniques and depth of anesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…We performed a post-hoc analysis of the data collected during the previous randomized clinical trial by Gajniak et al carried out at the university hospital in Poland between February 2019 and July 2022 [ 11 ]. The original study was approved by the Medical University of Silesia’s Ethics Committee in Katowice, Poland (KNW/0022/KB1/1/19) and registered at ClinicalTrials.gov (registration number NCT04691726).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations